Fibroblast Activation Protein Specific Optical Imaging in Non-Small Cell Lung Cancer - Mathieson, Layla; O’Connor, Richard A.; Stewart, Hazel; Shaw, Paige; Dhaliwal, Kevin; Williams, Gareth O. S.; Megia-Fernandez, Alicia; Akram, Ahsan R. (Frontiers in Oncology, 2022)
Fibroblast activation protein (FAP) is a cell surface propyl-specific serine protease involved in the regulation of extracellular matrix. Whilst expressed at low levels in healthy tissue, upregulation of FAP on fibroblasts can be found in several solid organ malignancies, including non-small cell lung cancer, and chronic inflammatory conditions such as pulmonary fibrosis and rheumatoid arthritis. Their full role remains unclear, but FAP expressing cancer associated fibroblasts (CAFs) have been found to relate to a poor prognosis with worse survival rates in breast, colorectal, pancreatic, and non-small cell lung cancer (NSCLC). Optical imaging using a FAP specific chemical probe, when combined with clinically compatible imaging systems, can provide a readout of FAP activity which could allow disease monitoring, prognostication and potentially stratify therapy. However, to derive a specific signal for FAP any sequence must retain specificity over closely related endopeptidases, such as prolyl oligopeptidase (PREP), and be resistant to degradation in areas of active inflammation. We describe the iterative development of a FAP optical reporter sequence which retains FAP specificity, confers resistance to degradation in the presence of activated neutrophil proteases and demonstrates clinical tractability ex vivo in NSCLC samples with an imaging platform.